Disclosure of Medical Error: Objective Structured Clinical Examination (OSCE) - Jumana Antoun; Maya Romani; Basem Saab (MedEdPORTAL, 2012)
Abstract Medical curricula has increasingly highlighted the important of assessing medical error disclosure skills of residents. This resource is a standardized patient case used in an objective structured clinical exam (OSCE) station to assess the communication skills of family medicine residents when disclosing a medical error to a patient. It was developed to be used with a standardized patient and an examiner. The case scenario and examiner checklist are included. The residents gave excellent verbal feedback on the importance of this OSCE station in medical error disclosure. They were also satisfied with the standardized patients. Almost all of them were impressed with his skills and his ability to portray realism. The OSCE was videotaped and was evaluated by two faculty members with an interraterreliability of 0.816.